Pengaruh Harga, Promosi dan Kualitas Pelayanan Terhadap Niat Berkunjung Kembali (Studi pada Kubu Manggala Villa Seminyak) - I Gede Bagus Mas Anggastya Prana; Putu Yudi Setiawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The increasing intention to visit, especially in the field of tourism accommodation that provides lodging services and facilities greatly supports the needs and development of people’s lifestyles today. The purpose of this study was to analyze the impact of price, promotion, and service quality on the intention to revisit Kubu Manggala Villa Seminyak. This study was conducted at Kubu Manggala Villa Seminyak using multiple linear regression analysis. The sample used was 112 respondents obtained through the purposive sampling method. The results of the analysis showed that price has a positive and significant effect on the intention to revisit Kubu Manggala Villa Seminyak. Likewise, promotion and service quality also showed a positive and significant effect on the intention to revisit. Overall, price, promotion, and service quality contribute positively and significantly to the intention to revisit Kubu Manggala Villa Seminyak. Suggestions that can be recommended by the management of Kubu Manggala Villa Seminyak must pay attention to the pricing of each facility provided to tourists, such as discounts for tourists who stay more than 2 days, vouchers and bonuses given to tourists who stay. Advertising as a promotion to tourists must display the uniqueness of the villa itself as an example of what are the advantages with an attractive image display, the advantages of the product that tourists get when staying at Kubu Manggala Villa Seminyak by utilizing electronic media such as Instagram, Facebook, YouTube so that the advertisement has an interest for tourists who see it. The management in improving the quality of service must pay attention to every knowledge possessed by its employees, both in terms of products and services, this can be done by providing training and training so that employees are able to master the knowledge, skills, and attitudes that are emphasized to apply them in daily work activities.